Pengaruh Pemberian Diet Tinggi Lemak Terhadap Profil Lipid dan Gula Darah Puasa Serum Tikus Putih (Rattus Norvegicus) Galur Wistar - Indriputri, Cut; Maulana, Reza (HIGIENE: Jurnal Kesehatan Lingkungan, 2022)
Currently, many studies have proven that excessive fat consumption can trigger various disorders, such as obesity, dyslipidemia, hypertension, impaired glucose tolerance. This study aimed to examine the effect of a high-fat diet on lipid profiles and fasting blood sugar in the serum of white rats (Rattus norvegicus) Wistar strain. This study is a true experimental study with a randomized posttest-only control group design using 31 male Wistar rats weighing 150-250 grams, aged 4-5 months. Rats were divided into two groups, namely group K1 (negative control, normal diet) amounted to 7 and K2 (high-fat diet, with daily fat content of 66.28%) amounted to 24 mice. A high-fat diet was given for 50 days. The parameters examined were triglyceride levels, HDL cholesterol, and fasting blood sugar. The K1 group had an average triglyceride level of 52.16 mg/dL, HDL cholesterol 51.80 mg/dL, and fasting blood sugar 157.20 mg/dL; while the K2 group had an average triglyceride level of 101.00 mg/dL, HDL cholesterol 42.93 mg/dL, and fasting blood sugar 208.00 mg/dL. Based on the results of independent T-test analysis, the levels of triglycerides, HDL cholesterol, and fasting blood sugar in groups K1 and K2 were significantly different, namely 0.030, 0.011 and 0.009, respectively (P < 0.05). It can be concluded that a high-fat diet affects the lipid profile and fasting blood sugar. Keywords: high-fat diet, lipid profile, triglyceride, HDL cholesterol, fasting blood sugar, Rattus norvegicus